KEJADIAN MISSFILE REKAM MEDIS RAWAT INAP DI RUMAH SAKIT TKXY BANJARMASIN - Indah Noor Safitri; Husin Husin (UPPM Politeknik Unggulan Kalimantan, 2023)
Inappropriate medical record storage systems cause misfiles. Human resources and facilities factors have a role in misfile incidents. Missfile is a medical record file that is lost and misplaced on the medical record file storage rack in the filling room. This research is a quantitative research with a descriptive approach. The number of medical records in 2021 that is accurate is 6176 medical records with a sample of all medical records. This study obtained data on medical record missfile incidents as much as 1.81% of files, while the factors that play a role in misfile incidents are human resource factors, policies and medical record storage systems. In making efforts to prevent the occurrence of medical record misfiles, it is necessary to strengthen the implementation of policies, increase the competence of officers and add storage shelves so that medical records do not accumulate